1993
DOI: 10.1055/s-2007-1002105
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive GHRH Administration Fails to Increase the Response to GHRH in Obese Subjects

Abstract: Spontaneous GH secretion as well as GH response to several stimuli including GHRH have been shown to be reduced in obesity. To clarify the pathogenesis underlying these alterations, in six obese patients (3 males and 3 females, age 20-44 yrs, BMI = 42.1 +/- 2.2) on unrestricted diet we studied the effect of 8 day GHRH pretreatment (1 micrograms/kg iv each day) on the acute somatotropic response to the neurohormone administered both alone and combined with arginine (ARG, 0.5 g/kg iv infused from 0 to 30 min) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
6
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 25 publications
4
6
0
Order By: Relevance
“…On the other hand, also the existence of GHRH hypoactivity has been proposed in obesity; 8,39,40 this, in turn, could cause reduced GH synthesis and, thus, explain the reduction in the maximal secretory capacity of somatotrope cells and present data. 8,41 Other data, however, do not support the existence Figure 1 Mean ( s.e.m.)…”
Section: Discussionsupporting
confidence: 62%
“…On the other hand, also the existence of GHRH hypoactivity has been proposed in obesity; 8,39,40 this, in turn, could cause reduced GH synthesis and, thus, explain the reduction in the maximal secretory capacity of somatotrope cells and present data. 8,41 Other data, however, do not support the existence Figure 1 Mean ( s.e.m.)…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, human and animal studies provide compelling evidence to suggest that the hypothalamus may not be the principle site for altered GH secretion in obesity. Hypothalamic gene expression for GHRH and somatostatin does not change in dietaryinduced obese rats, regardless of pituitary insensitivity to GHRH (Cattaneo et al 1996), while chronic GHRH treatment coupled with arginine (to suppress endogenous SRIF release) does not recover GH secretion in dietaryinduced obese patients (Ghigo et al 1993). Consequently, it seems that impairments of GH secretion in obesity occur independent of changes in hypothalamic control of GH secretion.…”
Section: Discussionmentioning
confidence: 93%
“…21 In humans, we have found that 8 day GHRH pretreatment enhanced the low GH response to GHRH in elderly subjects but did not affect that in obese patients. 22 These ®ndings, however, do not de®nitively rule out the possibility that endogenous GHRH hypoactivity plays a critical role.…”
mentioning
confidence: 97%